Writing as Thinking in Paul's Letters. (6th January 2022) - Robertson, Paul
Abstract : This article uses findings from cognitive sciences and neuroscience to detail the unique brain processes that stem from writing texts by hand. Such findings are described and then applied to the case of the Christian apostle Paul, whose letters – penned by Paul himself and/or via a scribe – are often used as evidence in reconstructions of early Christian social contexts. An attention to the findings from cognitive sciences and neuroscience around what I term "handwriting-thinking", however, demonstrates a significant difference between the cognitive processes of Paul as author and the cognitive processes of his audience, who would have typically been exposed to Paul's letters aurally. This difference in cognitive processes between Paul and his audience significantly problematizes the usage of Paul's letters as evidence for his audience's understanding of his letters and the concepts therein. More broadly, an attention to the embodied cognition of handwriting-thinking demonstrates differences in conceptual understandings between historical text-producers and their audiences, suggesting that we should focus more on individual text producers and their contexts instead of audiences.